Pembelajaran PBL Berbasis Ethno-STEM dan Augmented Reality: Proses dan Respon Mahasiswa - Sari Saraswati; Meriana Wahyu Nugroho; Esty Saraswati Nur Hartiningrum (Universitas Islam Jember, 2026)
This study describes the implementation of Problem-Based Learning (PBL) using Ethno-STEM-based e-modules, assisted by Augmented Reality (AR), in the Integral Calculus course, and examines students' responses to the learning process and the development of critical thinking skills. The study employed a descriptive qualitative method with 37 Mathematics Education as subjects. The learning was designed by integrating local cultural contexts into AR-based STEM activities. Data were collected through critical thinking tests and student response questionnaires. The results showed that students' critical thinking skills were in the fair to good category, especially in the aspects of focus identification and reasoning, while the inference and reflection aspects still needed improvement. Students' responses to the learning process were very positive, especially in motivation, collaboration, and learning experiences. The integration of PBL, Ethno-STEM, and AR created contextual and meaningful learning. Keywords: Problem-Based Learning, Ethno-STEM, Augmented Reality